First three-dimensional skull of the Middle Triassic mixosaurid ichthyosaur Phalarodon fraasi from Svalbard, Norway ... - Roberts, Aubrey Jane; Engelschiøn, Victoria Sjøholt; Hurum, Jørn Harald (Plazi.org taxonomic treatments database, 2022)
This dataset contains the digitized treatments in Plazi based on the original journal article Roberts, Aubrey Jane, Engelschiøn, Victoria Sjøholt, Hurum, Jørn Harald (2022): First three-dimensional skull of the Middle Triassic mixosaurid ichthyosaur Phalarodon fraasi from Svalbard, Norway. Acta Palaeontologica Polonica 67 (1): 51-62, DOI: 10.4202/app.00915.2021, URL: http://dx.doi.org/10.4202/app.00915.2021 ...